Risk factors influencing Coxiella burnetii seropositivity in water Buffalo (Bubalus bubalis) populations of Egypt’s Nile Delta - Abdelfattah Selim; Mohamed Marzok; Hattan S. Gattan; Hesham Ismail (PLoS ONE, 2025)
This study investigated the seroprevalence of Coxiella burnetii in buffaloes across several governorates in Egypt’s Nile Delta. No significant variation was observed between regions (P > 0.05), although the highest prevalence was recorded in Kafr El-Sheikh (15.5%) and the lowest in Menofia (9.1%). While sex was not statistically significant, females showed a higher seroprevalence (12.4%) than males (9%). Age had a significant impact, with buffaloes over 8 years of age showed a higher prevalence (21.6%) compared to the younger age groups. Tick infestation was also significantly associated with infection, with a prevalence of 22.4% in infested animals. Buffaloes exposed to communal grazing (13.8%) or kept in contact with small ruminants (16.3%) showed increased seropositivity. Notably, animals with a history of abortion had a markedly higher prevalence (26.7%). Multivariate logistic regression analysis identified age above 8 years (OR = 6.7), tick infestation (OR = 3.0), contact with small ruminants (OR = 3.0), and abortion history (OR = 3.2) as significant risk factors. Communal grazing (OR = 1.9) and age between 5 and 8 years (OR = 2.2) were also associated with increased odds of seropositivity. These findings highlight key epidemiological factors contributing to C. burnetii infection risk in buffaloes.